ASSESSMENT OF CHANGE IN MODERATE TO VIGOROUS PHYSICAL ACTIVITY BY ACCELEROMETRY OVER TIME IN OBESE SUBJECTS: IS INDIVIDUAL ACCELEROMETER CUT POINTS USEFUL? - Eivind Aadland (Sport Scientific And Practical Aspects, 2025)
Objective To determine how the use of individual accelerometer cut points (ICPs) vs. a group-level cut point (GCP) affected the change in minutes of moderate-to-vigorous physical activity (MVPA) over a one-year lifestyle intervention for severely obese subjects. Design The study was an uncontrolled intervention study Method Based on a treadmill calibration protocol, we obtained cut points for MVPA (≥3 metabolic equivalents) for the Actigraph GT1M accelerometer in 42 subjects (11 men, body mass index 39.8 (5.7), age 43.2 (9.2) years). Of these, 23 to 28 subjects had valid assessments of change in MVPA over 4 measurements (baseline, week 4, week 16 and week 46). Results Change in MVPA from baseline to subsequent time-points did not differ (p = 0.649) and relationships between change in MVPA were moderate to strong (Spearman’s ρ = 0.77 to 0.93, p < 0.001) when MVPA was derived from the ICPs vs. the GCP. Still, the absolute differences in change in MVPA between the two cut point approaches were considerable. Conclusions The use of ICPs and the GCP to determine changes in MVPA over time yielded quite similar results, thus the most feasible cut point approach (to apply a GCP) might be preferred in future studies.